Role Performance of Agricultural Input Dealers in Agro-advisory Services in West Bengal - Amitava Panja; N. S. Shivalinge Gowda, D. V. Kusumalatha; Debi Kalyan Jayasingh (Indian Journal of Extension Education, 2022)
Agricultural input dealers, among many agencies in pluralistic extension systems, have the highest reach to farmers based on their location advantage, rapport building, and ease of accessibility. The study was conducted in two districts of West Bengal viz. Purba Bardhaman and Hooghly in 2020 to measure the role performance of agricultural input dealers in agro-advisory services. Eighty agricultural input dealers from these two districts were selected using random sampling procedure. Data was collected using personal interview method. Independent variables included personal and socio-economic, psychological, and communication variables. Majority of the variables were found to have a significant positive contribution to the role performance. In addition, variables such as cosmopoliteness, extension participation, credit orientation, information sharing behaviour, and types of inputs sold were found to have a significant positive contribution and explained about fifty-seven percent variation of the dependent variable. Path analysis showed that types of inputs sold had highest direct effect. Also, through this highest indirect effect of maximum variables had channelized